Participation in higher education in Australia among under-represented groups: What can we learn from the Higher Education Participation Program to better support Indigenous learners? - Smith, J.; Trinidad, Sue; Larkin, S. (2015)
In 1988 the release of the Higher Education: A Policy Statement White Paper focused Australia’s national higher education equity policy on “changing the balance of the student population to reflect more closely the composition of society as a whole” (Dawkins 1990, 2-3). While improvement in access and participation has been noted for women, people from non-English speaking backgrounds, and people with disabilities, the interventions has remained less effective for people from Lower Socio-Economic Status (LSES backgrounds), Indigenous peoples; rural, regional and remote residents; (Gale & Tranter, 2011; Koshy & Seymour 2014). In 2009, in response to the Bradley Review (2008), the Australian government set a new agenda again focused on equitable participation in higher education, along with associated equity targets (which have since been abandoned), and funding to enable this reform as well as increased participation. Funding was delivered through the Higher Education Participation and Partnerships Program (HEPPP), renamed the Higher Education Participation Program (HEPP) in 2015 (Australian Government Department of Education and Training, 2015). A range of national partnerships, policy initiatives and programs has been used to facilitate improved achievement in schools as well as enable access, participation and achievement in higher education. These actions have included targeted programs through the use of intervention strategies aimed at widening participation in, and improving access to higher education.